Time-resolved cathodoluminescence investigations of AlN:Ge/GaN nanowire structures. (13th July 2021) - Jungclaus, Jörgen; Spende, Hendrik; Hille, Pascal; Schörmann, Jörg; Waag, Andreas; Eickhoff, Martin; Voss, Tobias
Abstract: Light emitting diodes represent a key technology that can be found in many areas of everydays life. Therefore, the improvement of the efficiency of such structures offers a high economic and ecological potential. One approach is electrostatic screening of the quantum-confined Stark effect (QCSE) in polar III-V heterostructures by n-type doping in order to increase the oscillator strength of electronic transitions in quantum structures. In this study, we analyzed the cathodoluminescene (CL) spectra of different functional parts of individual AlN/GaN nanowire superlattices and studied their decay characteristics with sub-nanosecond time resolution. This allows us to extract information about strain and electric fields in such heterostructures with an overall spatial resolution <100 nm. The samples, which were investigated in a temperature range from 10 to 300 K by using time-integrated cathodoluminescence spectroscopy (TICL) and time-resolved cathodoluminescence spectroscopy (TRCL) consist of GaN bottom and top layer and a 40-fold stack of GaN nanodiscs, embedded in AlN barriers that were doped with Ge. We show, that the QCSE is reduced with increasing doping concentration due to a screening of the internal electric fields inside GaN nanodiscs, resulting in a reduction of the carrier lifetimes and a blue shift of the emitted light. Due to the small diameter of the electron excitation beam CL offers the possibility to individually analyze the different functional parts of the nanowires.